Retention Esophagitis as a Significant Clinical Predictor of Progression to Esophageal Cancer in Achalasia - Haewon Kim; Hyojin Park; HeeSeung Choi; Yooju Shin; Hyunsung Park; Young Hoon Youn; Jie-Hyun Kim (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims Chronic liquid and/or food stasis caused by retention esophagitis (RE) in achalasia is a notable endoscopic finding because of the presence of a thickened or whitish esophageal mucosa and histologically altered squamous hyperplasia. We aimed to identify the clinical features of RE associated with achalasia and to clarify the clinical definition of RE in achalasia as a precancerous lesion identified by analyzing biomarker expressions. Methods From 2006 to 2015, we retrospectively reviewed 37 patients with achalasia without previous treatment. Among them, 21 patients had diagnostic findings of RE (RE+) and 16 patients had no diagnostic findings of RE (RE-). Immunohistochemical staining of p53, p16, and Ki-67 was performed on the endoscopic biopsy tissues from the patients with achalasia and 10 control patients with non-obstructive dysphagia. Results The symptom duration and transit delay were significantly longer in the RE+ group than in the RE- group. We found particularly high p53 positivity rates in the RE+ group (p<0.001). The rate of p16 expression was also significantly higher in the RE+ group than in the other two groups (p=0.003). Conclusions A high p53 expression rate was more frequently found in the RE+ group than in the other two groups. RE could be a meaningful clinical feature of achalasia for predicting esophageal carcinogenesis.